Simultaneous Determination of Chromium(VI) and Manganese(VII) by Differential Kinetic Rate Spectrophotometry of Direct Yellow Brown D3G - Zhang, Dong (Asian Journal of Chemistry, 2012)
In this study, the fading reaction of Cr(VI) and Mn(VII) oxidating direct yellow brown D3G, a textile dyes, was investigated. In sulfuric acid medium, at 90 in water bath, both Cr(VI) and Mn(VII) could fade direct yellow brown D3G, but the fading rate was different. Moreover, there was no obvious synergistic effect between them. A new method to determine Cr(VI) and Mn(VII) by differential reaction rate kinetic direct yellow brown D3G fading spectrophotometry was purposed. The effect of medium acidity, the dosage of direct yellow brown D3G, reaction temperature and time on fading reaction was studied and the proportion equation was established. This method could be used to determine Cr(VI) and Mn(VII) in industrial wastewater and the results were according to the flame atomic absorption spectrophotometry.